Of the nuns, the priests, the crosses (Journal of Parents and Teachers, 1996)
The paper addresses personal issues related to identity and individual experience, as well as research in a laboratory. Specific techniques and references to Don Burgost and the Nuclear Power Plant are mentioned. In addition, the importance of design and creativity in the work is emphasized.
Keywords: identity; research; design; creativity